2020
DOI: 10.1016/j.eja.2020.126131
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability in Italian rice germplasm

Abstract: Plant breeding is one of the key strategies for further enhancement of crop yields; however, effective breeding strategies require phenotypic characterisation of the available germplasm. This study sought to characterise the phenotypic expression of fourteen crop traits related to phenology, plant architecture, and yield in a panel of 40 cultivars selected to represent the phenotypic variability present in Italian rice germplasm during a two-season field experiment. The observed range of phenotypic variation w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 65 publications
1
9
0
1
Order By: Relevance
“…The relationship among the traits was further investigated using principal component analysis, to determine the strength and direction of correlation between the original traits and their corresponding principal components (PCs) (Mongiano et al, 2020). The proportion of variance, cumulative proportion and eigenvalues were given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship among the traits was further investigated using principal component analysis, to determine the strength and direction of correlation between the original traits and their corresponding principal components (PCs) (Mongiano et al, 2020). The proportion of variance, cumulative proportion and eigenvalues were given in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge of the accessible genetic variability and complex relationships between the traits of interest are essential for all the crop improvement techniques. Morphological characterization of existing traditional germplasm is essential for the creation of new improved rice varieties that can aid rice systems in achieving greater economic and environmental sustainability (Mongiano et al, 2020). (Oyelola et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in these characteristics are critical for varietal identification and selection, and breeders need suitable knowledge of tomato genetic diversity to identify and improve tomato genotypes with desirable characteristics in terms of agricultural traits, disease resistance, harvest yield and quality (Fernandes et al 2018, Rosenqvist et al 2019. Moreover, the development of phenotypic-genetic markers that are closely linked to EB disease resistance facilitates the introgression of phenotypic traits into marker-assisted selection in resistance breeding and identification of resistant tomato genotypes (Mongiano et al 2020, Nafisa et al 2020. Therefore, the morphological and genetic characterization of tomatoes is needed to identify and conserve EB-resistance sources (Mata-Nicolás et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that global rice production should necessarily increase by approximately 20% by 2030 and 30% by 2050 at the rate of 0.6–1% increase annually to meet the demands of the growing population projected to result from rapid population growth, and economic and industrial developments ( Peng et al, 2009 ; Shew et al, 2019 ). Investigating various strategies to increase grain yield in rice has been a key research focus of agronomists for many years ( Shew et al, 2019 ; Mongiano et al, 2020 ; Zhao et al, 2020 ; Xu et al, 2021 ). During recent decades, most of the rice-growing regions experienced an obvious warming trend across the globe, and this trend is projected to change the duration of rice growth and undermine the grain yield ( Liu et al, 2013 ; Raza et al, 2019 ; Fatima et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%